Association of Human DEAD Box Protein DDX1 with a Cleavage Stimulation Factor Involved in 3′-End Processing of Pre-mRNA - Bléoo, Stacey (The American Society for Cell Biology, 2001)
DEAD box proteins are putative RNA helicases that function in all aspects of RNA metabolism, including translation, ribosome biogenesis, and pre-mRNA splicing. Because many processes involving RNA metabolism are spatially organized within the cell, we examined the subcellular distribution of a human DEAD box protein, DDX1, to identify possible biological functions. Immunofluorescence labeling of DDX1 demonstrated that in addition to widespread punctate nucleoplasmic labeling, DDX1 is found in discrete nuclear foci ∼0.5 μm in diameter. Costaining with anti-Sm and anti-promyelocytic leukemia (PML) antibodies indicates that DDX1 foci are frequently located next to Cajal (coiled) bodies and less frequently, to PML bodies. Most importantly, costaining with anti-CstF-64 antibody indicates that DDX1 foci colocalize with cleavage bodies. By microscopic fluorescence resonance energy transfer, we show that labeled DDX1 resides within a Förster distance of 10 nm of labeled CstF-64 protein in both the nucleoplasm and within cleavage bodies. Coimmunoprecipitation analysis indicates that a proportion of CstF-64 protein resides in the same complex as DDX1. These studies are the first to identify a DEAD box protein associating with factors involved in 3′-end cleavage and polyadenylation of pre-mRNAs.